Tingkah Laku Makan Sapi Peranakan Ongole yang Diberi Pakan Berbasis Jerami Padi Amoniasi Dengan Metode Pemberian yang Berbeda - Muhamad Bata; Akhmad Sodiq (Jurnal Agripet, 2014)
(Feeding behavior of local cattle fed based ammoniation rice straw with different feeding method)ABSTRACT. The objective of this study was to determine the effect of feeding methods on feeding behavior include the frequency and duration of eating time, the frequency and the duration of rumination for one day, night and daytime. The study used twenty of local cattle feeder males (Peranakan Ongole) with an age range of 1.5 2 years old and initial weight were 200-273 kg. They were fed randomly with four feeding methods of top concentrate, component feeding, total mixed ration (TMR) and free choice. Thus, completely randomized design was used for this study. Data length of eating and rumination time was analyzed using analysis of variance and continuities by honestly significant difference test (HSD). The frequency of eating and rumination were analyzed using Chi square. The results showed that the treatments affect significantly (P 0.05) on spent of eating night; rumination daytime and night spent, but had no effect (P0,05) on spent of eating one day, spent of eating daytime and spent of rumination for one day. Rumination frequency one day, daytime, and night were not affected (P 0.05) by feeding method. Night rumination of feeder cattle groups fed with TMR method were longer ( P 0.05 ) compared to feeder cattle groups fed with Component Feeding and Free Choice method, but it was similar ( P 0.05 ) to feeder cattle groups fed with Top Concentrate. Between the groups feeder cattle fed with Component feeding and Free Choice were not significantly different ( P 0.05 ).